THE OLDEST GRANITOIDS IN THE TRANSANGARA REGION OF THE YENISEI RIDGE: U-TH-PB DATA ON ZIRCON - Vernikovskaya A.E.; Vernikovsky V.A.; Popov N.V.; Yasenev A.M.; Wingate M.T.D. (My University, 2004)
It is established that in Transangara distinctly specified is the most early Neoproterozoic collision event in the range of 865-880 mln years ago. According to the determined geologic position, chemical composition and granitoids formation age, the integral Teiskii complex includes, apart from the considered Teiskii and Kalaminskii massifs, granites of Erudinskii massif with the age 878 mln years. Most likely, the granites of this complex were formed outside Siberian shield, being within Central-Angara terrein already before its collision with Siberia.